CHARACTERISTICS AND MATERNAL-PERINATAL OUTCOMES IN WOMEN WITH SEVERE PREECLAMPSIA AT SUMBER WARAS HOSPITAL - Odilia, Nina Edhita; Hidayat, Fadil; Liedapraja, Mediana Sutopo (E-Jurnal Medika Udayana; Vol 13 No 10 (2024): E-Jurnal Medika Udayana, 2024)
Preeclampsia is a cause of high maternal and fetal morbidity and mortality in developing countries. According to the Indonesian Health Profile, in 2021, hypertension in pregnancy is the second most common cause of maternal death in Jakarta with 22 cases out of 152 deaths. This study aims to determine the characteristics and maternal and perinatal outcomes of severe preeclampsia patients at Sumber Waras Hospital. This study was conducted in a descriptive qualitative observational manner with a cross-sectional approach using secondary data from medical records of patients with severe preeclampsia. The number of samples in this study was 85 pregnant women using a total sampling method on all pregnant women with severe preeclampsia who gave birth at Sumber Waras Hospital in the period January 2022 - December 2023. In this study, it was found that the majority of mothers with severe preeclampsia were aged 18-35 years. (63.5%), BMI in the second-degree obesity category (43.5%), multiparous parity status (64.7%), and term gestational age (76.5%). Maternal outcomes that occurred included eclampsia (14.1%), HELLP syndrome (2.4%), visual impairment (10.6%), and pulmonary edema (1.2%). The majority of perinatal outcomes had live babies (98.8%), no asphyxia (88.2%), and babies with normal weight (78.8%). Severe preeclampsia at Sumber Waras Hospital occurs more often in pregnant women aged 18-35 years, with a second-degree obesity BMI, multiparous, and term. Meanwhile, the outcomes that occurred were eclampsia, HELLP syndrome, visual disturbances, pulmonary edema, live babies, babies without asphyxia, and normal-weight babies. Keywords: Severe Preeclampsia., Characteristics., Outcomes